2008
DOI: 10.1016/j.jacc.2008.07.025
|View full text |Cite
|
Sign up to set email alerts
|

Localization of Atrial Fibrillation Triggers in Patients Undergoing Pulmonary Vein Isolation

Abstract: Reproducible spontaneous and provoked PV triggers initiating AF can be observed in most patients undergoing AF ablation. These triggers most commonly originate from the carina region of both right and left PVs. Noncarina PV triggers more commonly require provocation with isoproterenol infusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(53 citation statements)
references
References 25 publications
2
50
1
Order By: Relevance
“…Particularly, the mid-PV opening may enhance tissue non-uniformity in the carina of right PV openings 3 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Particularly, the mid-PV opening may enhance tissue non-uniformity in the carina of right PV openings 3 .…”
Section: Discussionmentioning
confidence: 99%
“…One possible mechanism underlying the recurrence may be the reconnection of ablated atrial musculature surrounding the PV openings 3 . In addition to the technical challenges, the tissue architecture of the left atrium may be involved in ablation line reconnection 4 .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Valles et al reported the importance of spontaneous PV triggers (accounting for 63% of all triggers) originating from the carina region in patients undergoing AF ablation. 34 Wongcharoen et al also found that 15% of AF patients had roof pouches and a longer roof line. 35 The location of the LA appendage and left PVs may affect catheter stability during the ablation, and an inferior LA appendage is more frequently observed in AF patients.…”
Section: Anatomical Identification and Integration Of Non-invasive Immentioning
confidence: 94%
“…1,[6][7][8] In persistent AF, if triggers are specifically searched before ablation, most of them are also situated in the pulmonary veins. [9][10][11] Results from pharmacological and electrophysiological studies in animals and humans have yielded conflicting results regarding the mechanism of pulmonary vein firing.…”
Section: Trigger Ablation In Persistent Afmentioning
confidence: 99%
“…1,8,11 Once a trigger is identified, it has to be mapped and ablated. This can be very challenging, especially when multiple triggers are present.…”
Section: Trigger Ablation In Persistent Afmentioning
confidence: 99%